Zeolites Catalyze the Nazarov Reaction and the tert-Butylation of Alcohols by Stabilization of Carboxonium Intermediates - Tejeda-Serrano, María; Sanz-Navarro, Sergio; Blake, Finn; Leyva-Pérez, Antonio (Synthesis, 2020)
Zeolites are the most used catalysts worldwide in petrochemistry processes, with particular ability to stabilize carbocations. However, the use of zeolites in organic synthesis is still scarce. We show here that representative carboxonium-mediated organic reactions, such as the Nazarov cyclization and the tert-butylation of alcohols with tert-butyl acetate, typically performed with very strong acid catalysts in solution such as triflic acid, can be catalyzed by simple zeolites with high yield and selectivity. The aluminosilicate framework stabilizes the intermediate carboxonium species and overrides the need for superacid protons in solution.
Keywords: zeolites; solid catalyst; Nazarov reaction; tert-butylation reaction; carboxonium; heterogeneous catalysis